Understanding Infrastructure Edge Computing: Concepts, Technologies, and Considerations - Marcham, Alex (2021)
"This book is intended to provide the reader with a thorough understanding of the growth in internet infrastructure since its inception, through to the emerging set of technologies known as infrastructure edge computing which progress this trend to its next generation. Infrastructure edge computing is the term coined by the author (and now accepted by the Linux Foundation and their LF Edge group, as well as much of the industry) for a model of data center and network infrastructure deployment which distributes a large number of physically small data centers around an area to provide users with superior performance than is achievable today, to enable a range of new use cases in an economical fashion. These use cases include 5G (Fifth Generation) mobile cellular networks, city-scale AI (Artificial Intelligence) systems which can help us work and play more effectively by automating many time-consuming tasks, and cyber-physical systems such as self-driving cars, drones and industrial robotics systems to save time, save money and improve safety. To provide the reader with a full understanding of the subject, the book will cover several topics from today?s state of the art to how the infrastructure edge computing model alters that to the key technologies underpinning its deployment and operation, through to the use cases which it will support that are impractical or impossible on current infrastructure. The end result is to provide the reader with a thorough, accessible and accurate understanding of the next generation of internet infrastructure as a whole"--
Keywords: Edge computing